The Balance of Power - Luard, Evan. author. aut Link
XVI, 399 p.
Keywords: This book examines on an analytical basis the system of international relations between 1648 and 1815. It considers the character of the states, their principal foreign policy goals and the beliefs that influences their relations. The author seeks on this basis to examine the character of the system as a whole: in particular how from the proclaimed desire to maintain the 'balance of power' it succeeded in establishing international stability in preventing the domination of particular states.